(untitled) (Ar Rehla: Journal of Islamic Tourism Halal Food Islamic Traveling and Creative Economy, 2025)
Abstract: The development of the creative economy in Malang City is supported by the emergence of local culinary businesses such as Kanenakan, which utilize digital technology in their marketing activities. The culinary sector is one of the most in-demand subsectors of the creative economy today, due to its potential to drive innovation and local economic growth. This study aims to analyze the influence of Electronic Word of Mouth (E-WOM) and customer reviews on purchase decisions, with purchase intention as a mediating variable, while also exploring how these findings contribute to the development of the creative economy, particularly in the local culinary sector. A quantitative approach was employed through a survey of 135 respondents. The results indicate that customer reviews significantly influence purchase decisions, both directly and indirectly through purchase intention. In contrast, E-WOM does not have a significant effect. These findings highlight the importance of authentic customer reviews in supporting purchase decisions and sustaining local creative businesses. The implications suggest that optimizing customer experience can be a key strategy in strengthening the creative economy ecosystem in Malang. Keywords: creative economy; electronic word offmouth (e-wom); customer review; purchase decision; purchase intention. Abstract: Perkembangan ekonomi kreatif di Kota Malang didukung oleh hadirnya bisnis kuliner lokal seperti Kanenakan, yang memanfaatkan teknologi digital dalam aktivitas pemasarannya. Kuliner merupakan salah satu subsektor ekonomi kreatif yang saat ini banyak diminati masyarakat karena potensinya dalam mendorong inovasi dan pertumbuhan ekonomi lokal. Penelitian ini bertujuan untuk menganalisis pengaruh Electronic Word of Mouth (E-WOM) dan ulasan pelanggan terhadap keputusan pembelian, dengan minat beli sebagai variabel mediasi, serta melihat bagaimana temuan tersebut dapat memberikan kontribusi terhadap pengembangan ekonomi kreatif, khususnya di sektor kuliner lokal. Penelitian menggunakan pendekatan kuantitatif dengan teknik survei terhadap 135 responden. Hasil analisis menunjukkan bahwa ulasan pelanggan berpengaruh signifikan terhadap keputusan pembelian, baik secara langsung maupun melalui minat beli sebagai mediasi. Sebaliknya, E-WOM tidak memberikan pengaruh yang signifikan. Temuan ini menekankan pentingnya ulasan pelanggan yang otentik dalam mendukung keputusan pembelian serta keberlangsungan usaha kreatif lokal. Implikasi dari penelitian ini menunjukkan bahwa optimalisasi pengalaman pelanggan dapat menjadi strategi penting dalam memperkuat ekosistem ekonomi kreatif di Malang. Keywords: ekonomi kreatif; electronic word of mouth (e-wom); ulasan pelanggan; keputusan pembelian; minat beli.